Radial force control for triple three-phase sectored SPM machines. Part II: Open winding fault tolerant control - Sala, Giacomo; Gerada, David; Gerada, C.; Tani, A. (2017)
A new advanced fault tolerant control technique for a triple three-phase Surface Permanent Magnet (SPM) machine is investigated in this paper. The machine has a nine-phase winding arranged in three sectors and supplied by three different Voltage Source Inverters (VSIs). The proposed current control technique is firstly exploited to avoid the radial force appearance in case of open winding of one machine sector. Then, the radial force fault tolerant control is improved to compensate for a bearing fault or another source of radial force in this open winding condition. Finite element simulations are used to validate the two proposed control techniques. Finally, advantages and drawbacks of the solution are highlighted.